Antihypertensive Treatment and Central Arterial Hemodynamics: A Meta-Analysis of Randomized Controlled Trials - Cheng, Yi-Bang; Xia, Jia-Hui; Li, Yan; Wang, Ji-Guang (Frontiers in Physiology, 2021)
Background: Antihypertensive treatment may have different effects on central arterial hemodynamics. The extent of the difference in effects between various antihypertensive drugs remains undefined. Methods: We conducted a systematic review and meta-analysis of randomized controlled trials that explored the effects of antihypertensive agents on both central and peripheral systolic blood pressure (SBP) and pulse pressure (PP) or central augmentation index, with a special focus on the comparison between newer [renin-angiotensin-aldosterone system (RAS) inhibitors and calcium-channel blockers (CCBs)] and older antihypertensive agents (diuretics and β- and α-blockers). Results: In total, 20 studies (n = 2,498) were included. Compared with diuretics (10 studies), β-blockers (16 studies), or an α-blocker (1 study), RAS inhibitors (21 studies), and CCBs (6 studies) more efficaciously (P < 0.001) reduced both central and peripheral SBP by a weighted mean difference of −5.63 (−6.50 to −4.76 mmHg) and −1.97 mmHg (−2.99 to −0.95 mmHg), respectively. Compared with older agents, the newer agents also more efficaciously (P < 0.001) reduced central PP (−3.27 mmHg; −4.95 to −1.59 mmHg), augmentation index (−6.11%; −7.94 to −4.29) and augmentation (−3.35 mmHg; −5.28 to –1.42 mmHg) but not peripheral PP (p ≥ 0.09). Accordingly, the newer agents reduced central-to-peripheral PP amplification significantly less than the older agents (0.11 mmHg; 0.05 to 0.17 mmHg; P < 0.001). Conclusion: Newer agents, such as RAS inhibitors and CCBs, were significantly more efficacious than older agents in their effects on central hemodynamics.